Acute acalculous cholecystitis complicating systemic lupus erythematosus: case report and review. Issue 6361 (22nd January 1983) - Swanepoel, C R; Floyd, A; Allison, H; Learmonth, G M; Cassidy, M J; Pascoe, M D
Abstract : A case of acalculous cholecystitis presented as an acute abdominal emergency in a 22 year old woman with severe systemic lupus erythematosus. At the time of presentation the patient was receiving high doses of prednisone and cyclophosphamide to control her underlying disease. Histological examination of the biopsy specimen from the gall bladder showed lupus vasculitis. This complication of systemic lupus erythematosus has not been reported before. Laboratory studies and changes in lupus activity may fail to predict the onset of cholecystitis.